Bacterial Aetiology and Antibiotic Resistance Pattern of Community-Acquired Urinary Tract Infections in Children in a Tertiary Care Hospital in Bangladesh (Journal of Enam Medical College, 2017)
Background: Urinary tract infections (UTIs) in children are among the most common bacterial infections. Community-acquired urinary tract infections (CAUTI) are often treated empirically with broad-spectrum antibiotics. Pattern of aetiologic agents and their antibiotic sensitivity may vary according to geographical and regional location. So, knowledge of antibiotic resistance trends is important for improving evidence-based recommendations for empirical treatment of UTIs.Objectives: To determine the common bacterial aetiologies of CAUTIs and their antibiotic resistance patterns in a tertiary care hospital, Savar.Materials and Methods: This cross-sectional descriptive study was conducted at Enam Medical College Hospital, Savar from May 2016 to April 2017. We collected clean-catch mid-stream urine samples from 257 patients having clinical diagnosis of UTI and submitted to the clinical microbiology laboratory for culture and sensitivity.Results: A total of 120 (46.7%) samples were positive for bacterial growth. Escherichia coli (79%) was the most common pathogen, followed by Klebsiella spp. (14%). Bacterial isolates showed high prevalence of resistance to multiple antibiotics. Resistance against amoxicillin/clavulanic acid, co-trimoxazole and ciprofloxacin was higher compared to newer quinolones and aminoglycosides.Conclusion: Esch. coli and Klebsiella spp. were the predominant bacterial pathogens. The resistance pattern to commonly prescribed antibiotics was quite high and alarming.J Enam Med Col 2017; 7(3): 134-139